Peran Guru Bimbingan Konseling Dalam Mengatasi Tantangan Siswa: Studi Layanan Dan Kegiatan Konseling Di Smp N 6 Metro - Ahmad Mukhlishin; Anisa Putri Muda (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2024)
Abstract : This study focuses on the role of guidance and counseling teachers in overcoming student challenges at SMP N 6 Metro. This study uses qualitative research methods, such as interviews and observations, to evaluate the guidance and counseling services provided by these teachers. The results showed that guidance and counseling teachers have an important role in improving students' academic achievement, then they help students overcome mental and emotional health problems, as well as create a better learning environment In addition, this study also found that guidance and counseling teachers can reduce students' level of loss, which is interpreted by their involvement in the learning process. In the context of this study, guidance and counseling teachers play a key role in education. They not only provide academic support, but also help students overcome challenges they face, such as stress, worries, and mental health issues. By conducting individual and group counseling and providing counseling services for the school community, guidance and counseling teachers help students develop social and emotional competencies and prepare them for future challenges. Overall, this study shows that the role of guidance and counseling teachers in overcoming student challenges at SMP N 6 Metro is very important. By understanding and utilizing this role, guidance and counseling teachers can help students achieve their academic and non-academic success. Keyword: Guidance and Counseling, Implementation of Guidance and Counseling, Students